How students and specialists appreciate the mini-clinical evaluation exercise (mini-CEX) in Indonesian clerkships - Yoyo Suhoyo; Johanna Schönrock-Adema; Ova Emilia; Jan B. M. Kuks; Janke Cohen-Schotanus (BMC Medical Education, 2020)
Abstract Background Cultural differences might challenge the acceptance of the implementation of assessment formats that are developed in other countries. Acceptance of assessment formats is essential for its effectiveness; therefore, we explored the views of students and specialists on the practicality and impact on learning of these formats. This study was conducted to explore Indonesian students’ and specialists’ appreciation of the implementation of the Mini-Clinical Evaluation Exercise (Mini-CEX) in Indonesian clerkships. Methods This study was conducted at the Universitas Gadjah Mada, Indonesia. Participants were 52 students and 21 specialists in neurology and 78 students and 50 specialists in internal medicine. They were asked to complete a 19-item questionnaire that covered the characteristics of the mini-CEX such as its practicality, and the impact on learning and professional development. We used a Mann-Whitney U test to analyse the data. Results In total, 124 students (46 from neurology and 78 from internal medicine) and 38 specialists (13 from neurology and 25 from internal medicine) participated in this study. Students and specialists were positive about the practicality of the mini-CEX and the impact of this assessment format on learning and on professional development. The Mann-Whitney U test showed that there were no significant differences between students’ and specialists’ opinions on the mini-CEX, except for 2 items: specialists’ appreciation of direct observation (mean rank = 93.16) was statistically significantly higher than students’ appreciation of it (mean rank = 77.93; z = 2.065; p < 0.05), but students’ appreciation of the item that students’ past mini-CEX results affected their recent mini-CEX outcomes (mean rank = 85.29) was significantly higher than specialists’ appreciation of it (mean rank = 69.12; z = 2140; p < 0.05). Conclusion Students and specialists were positive about the mini-CEX in Indonesian clerkships, although it was developed and validated in another culture. We found only small differences between their appreciations, which could be explained by the patterns of specialist-student interaction in Indonesian culture as large power distance and low individualism country.